2000
DOI: 10.1046/j.1460-9568.2000.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of mixed glycine and GABAergic synapses in cultured spinal cord neurons

Abstract: In the spinal cord, GABA and glycine mediate inhibition at separate or mixed synapses containing glycine and/or GABAA receptors (GlyR and GABAAR, respectively). We have analysed here the sequence of events leading to inhibitory synapse formation during synaptogenesis of embryonic spinal cord neurons between 1 and 11 days in vitro (DIV). We used immunocytochemical methods to detect simultaneously an antigen specific to inhibitory terminals, the vesicular inhibitory amino acid transporter (VIAAT), and one of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 57 publications
7
64
0
2
Order By: Relevance
“…Under these conditions, the vast majority of the dendritic vege(2) clusters (80.5 Ϯ 3.5%) colocalized with the presynaptic marker FM4-64 (Fig. 2 A), in agreement with previous results on the colocalization of gephyrin with endogenous GlyR clusters or the vesicular transporter protein VIATT at inhibitory synapses (Dumoulin et al, 2000;Bedet et al, 2006;Hanus et al, 2006). We could, therefore, directly image synaptic gephyrin clusters in living neurons, avoiding fixation and immunolabeling of the receptor.…”
Section: Interference With Gephyrin Clustering In Spinal Cord Neuronssupporting
confidence: 90%
“…Under these conditions, the vast majority of the dendritic vege(2) clusters (80.5 Ϯ 3.5%) colocalized with the presynaptic marker FM4-64 (Fig. 2 A), in agreement with previous results on the colocalization of gephyrin with endogenous GlyR clusters or the vesicular transporter protein VIATT at inhibitory synapses (Dumoulin et al, 2000;Bedet et al, 2006;Hanus et al, 2006). We could, therefore, directly image synaptic gephyrin clusters in living neurons, avoiding fixation and immunolabeling of the receptor.…”
Section: Interference With Gephyrin Clustering In Spinal Cord Neuronssupporting
confidence: 90%
“…These results support the notion that GlyRs tracked at FM4-64-stained synapses were mainly located at inhibitory synapses. This is consistent with (1) the predominance of inhibitory contacts on spinal cord neurons (Dumoulin et al, 1999) and (2) the low probability of finding GlyRs at excitatory synapses where they are not accumulated (Dumoulin et al, 2000).…”
Section: Distinct Effects Of F-actin and Mictrotubule Disruption On Gsupporting
confidence: 86%
“…We were unable to determine whether GABARs or gephyrin localize to synapses first in developing wild-type neurons, because we could consistently detect only both or neither. However, Dumoulin et al (2000) reported in spinal cord neurons that GABA A R localizes to synapses before gephyrin.…”
Section: Role Of Gephyrin In Synaptic Clustering Of Gaba a Rsmentioning
confidence: 99%